Non cognitive skills and personality traits: Labour market relevance and their development in education & training systems - Giorgio Brunello; Martin Schlotter (Institute for the Study of Labor (IZA), 2011)
This paper reviews the empirical economic literature on the relative importance of non cognitive skills for school and labour market outcomes, with a focus on Europe. There is evidence that high cognitive test scores are likely to result not only from high cognitive skills but also from high motivation and adequate personality traits. This suggests that part of the contribution of cognitive skills to economic growth could be due to personality traits. Across large parts of the literature, there is consensus that non cognitive skills have important effects both on school attainment and on labour market outcomes. These effects might be as important as the effects of cognitive skills. Less consensus exists on the malleability of non cognitive skills, with some arguing that these skills can be altered until the end of teenage years and others claiming that emotional intelligence can be changed at any age. Most of what economists know about the technology of non cognitive skill formation concerns early educational levels, such as preschools and schools. While it is difficult to argue that all relevant skill formation ends before labour market entry, there is scant evidence on the role of the workplace in the maintenance and development of existing skills. Clearly, more research in this area is needed.
urn:nbn:de:101:1-201106013933
Keywords: J24; 330; non cognitive skills; Europe